2021
DOI: 10.1364/ome.433734
|View full text |Cite
|
Sign up to set email alerts
|

Laser cladding of transparent fused silica glass using sub-µm powder

Abstract: Fused silica glass is a commonly used high-performance material. However, due to the high temperature necessary for its production, manufacturing can also be challenging and costly. An attractive approach is additive manufacturing through laser cladding. Laser cladding of transparent fused silica was achieved using a CO2-laser to locally melt the substrate while injecting a stream of fumed silica glass powder into the melt-pool. By the described technique, it is possible to manufacture fully sintered silica gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The larger separation mitigates the thermal expansion-related deformations and increases the lifespan of the nozzle. The performance of such a coaxial powder nozzle was discussed in detail in Maniewski et al 98 The typical, continuous printing rate demonstrated in our work was as high as 1.3 mm 3 /s when using a discrete coaxial nozzle. 92 Importantly, these rates were achieved using lab-scale setup, and they can be readily improved, for example, by employing more powerful laser enabling operating with larger spot sizes and higher scanning speeds.…”
Section: F I G U R E 6 Sketch Of Thermodynamics Of Lc (Equations 3-6)mentioning
confidence: 56%
See 3 more Smart Citations
“…The larger separation mitigates the thermal expansion-related deformations and increases the lifespan of the nozzle. The performance of such a coaxial powder nozzle was discussed in detail in Maniewski et al 98 The typical, continuous printing rate demonstrated in our work was as high as 1.3 mm 3 /s when using a discrete coaxial nozzle. 92 Importantly, these rates were achieved using lab-scale setup, and they can be readily improved, for example, by employing more powerful laser enabling operating with larger spot sizes and higher scanning speeds.…”
Section: F I G U R E 6 Sketch Of Thermodynamics Of Lc (Equations 3-6)mentioning
confidence: 56%
“…The transparent, pure fused silica coatings and highly densified three-dimensional structures obtained via LC were demonstrated in our earlier work. 98 The hot-zone dynamics that enabled deposition of highly densified silica-based glass are discussed below.…”
Section: Am: Laser Cladding (Lc) and Lpdmentioning
confidence: 99%
See 2 more Smart Citations
“…The molten silicon is easily visible in the neck down region to recrystallise the silicon core [7] and is comparable to estab-396 lished draw tower results [16]. the bulk of material is prepared in-house by DPD using sub-427 micron powders [18]. By careful mixing of dry powders, the 428 mechanical as well as optical properties of the sintered glass were engineered and tailored to application [19] using the titania to increase the refractive index of the glass [20].…”
mentioning
confidence: 99%